Comparative Life Cycle Assessment of Conventional Concrete to Ash Concrete - Ferreira, José (2021)
In the present work, the environmental impacts of the concrete made with woody fly ash that presented compressive strength like the conventional concrete were evaluated and compared using the Life Cycle Assessment methodology. The impact assessment method used was the “CML-IA baseline” implemented in SimaPro software. The results showed that concrete with fly ash had a lower impact than conventional concrete in all the impact categories under study and may be classified as an eco-material (eco-concrete) considering that the environmental issues that are minimized are waste reduction, reduce of landfill problems and resource saving by the utilization of recycled materials.